Digitalisasi Media Pembelajaran Kalam Melalui Aplikasi Tik Tok - dzun nur nafiah; Shofil Fikri (Tarling : Journal of Language Education, 2023)
Speaking skills are one of the most important language skills in the process of learning Arabic, especially for Arabic learners. This study aims to 1) describe digitization and learning media of Kalam and several applications that can support it; 2) explain the effective steps in the formation of Maharah Kalam learning media using the Tik-Tok Audio Visual application. The method used in this study is a qualitative descriptive research method using the library research method. This research is descriptive in nature and the data is collected in the form of words and pictures. The results of the discussion in this article are learning media design models using several applications to support Maharah Kalam learning such as Articular Story, Youtube, and Tik-tok applications. The stages in the tik-tok application can meet the criteria for interesting learning media for students, especially in learning Maharah Kalam Arabic. Of the several features above, its use can be implemented for Arabic learning media, especially Maharah Kalam. The tik-tok application can be an interactive medium for students, especially in the voice recording feature which can then be shared via social networks. This application can attract students because it has many features that can be implemented in learning. System that is always updated to follow the trend of the times.